Fetomaternal Outcome Associated With Oligohydramnios In Uncomplicated Term Pregnancies - Jabbar, Sana Abdul; Zahoor, Sadia; Zulfiqar, Sadia; Rafique, Sumbla (Biological and Clinical Sciences Research Journal, 2025)
Oligohydramnios, defined as an amniotic fluid index (AFI) ≤5 cm, is associated with adverse perinatal outcomes in term pregnancies. In resource-limited settings like Pakistan, the implications of this condition remain underexplored. This study investigates the fetomaternal outcomes associated with oligohydramnios in otherwise uncomplicated term pregnancies. Objective: To evaluate and compare the maternal and neonatal outcomes among term pregnant women with oligohydramnios (AFI ≤5 cm) and those with normal amniotic fluid levels (AFI >5 cm). Methods: A prospective cohort study was conducted at Sheikh Zayed Hospital, Rahim Yar Khan, from February to April 2025. A total of 112 pregnant women at 37–42 weeks of gestation were enrolled and divided into two groups: Group A (AFI ≤5 cm) and Group B (AFI >5 cm), each with 56 participants. Exclusion criteria included medical or obstetric complications and fetal anomalies. Primary outcomes measured included mode of delivery, birth weight, APGAR scores, intrauterine growth restriction (IUGR), meconium-stained liquor, NICU admissions, and neonatal death. Statistical analyses included Chi-square tests and relative risk (RR) calculations, with a p-value <0.05 considered significant. Results: Labor induction (53.6% vs. 30.4%, p=0.01) and cesarean delivery (60.7% vs. 32.1%, p=0.002) were significantly more frequent in the oligohydramnios group. Adverse neonatal outcomes such as low birth weight (32.1% vs. 10.7%, p=0.005), low APGAR scores at 5 minutes (17.9% vs. 5.4%, p=0.04), meconium-stained liquor (25.0% vs. 7.1%, p=0.01), IUGR (23.2% vs. 7.1%, p=0.02), and NICU admission (21.4% vs. 5.4%, p=0.01) were significantly higher in Group A. The highest relative risk was observed for NICU admissions (RR = 3.96), followed by meconium-stained liquor (RR = 3.50), and IUGR (RR = 3.27). Conclusion: Oligohydramnios in term pregnancies is significantly associated with increased rates of labor induction, cesarean delivery, and adverse neonatal outcomes, including low birth weight, lower APGAR scores, meconium-stained amniotic fluid, IUGR, and NICU admissions. These findings underscore the need for timely identification and close monitoring of such cases to improve fetomaternal outcomes.